2003
DOI: 10.4049/jimmunol.170.4.2004
|View full text |Cite
|
Sign up to set email alerts
|

TNF Plays an Essential Role in Tumor Regression after Adoptive Transfer of Perforin/IFN-γ Double Knockout Effector T Cells

Abstract: We have recently shown that effector T cells (TE) lacking either perforin or IFN-γ are highly effective mediators of tumor regression. To rule out compensation by either mechanism, TE deficient in both perforin and IFN-γ (perforin knockout (PKO)/IFN-γ knockout (GKO)) were generated. The adoptive transfer of PKO/GKO TE mediated complete tumor regression and cured wild-type animals with established pulmonary metastases of the B16BL6-D5 (D5) melanoma cell line. PKO/GKO TE also mediated tumor regression in D5 tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…Besides the two main killing pathways, it has been reported that other killing mechanisms, for example the proinflammatory cytokines gIFN and TNFa, have important roles in rejection of pulmonary metastasis of tumor cells. 38 In the study of Poehlein et al, 31 adoptive transfer of effector T cells, which are taken from perforin and gIFN double knockout mice (PKO/GKO), mediated complete tumor regression and cured wild-type animals with established pulmonary metastasis of melanoma cells by a TNF-a mediated killing mechanism. In addition, Smyth et al 39 have reported that, using the Renca carcinoma tumor model, TRAIL expression on NK and NKT cells has effective antimetastatic functions in vivo mediated by a gIFNdependent immune mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the two main killing pathways, it has been reported that other killing mechanisms, for example the proinflammatory cytokines gIFN and TNFa, have important roles in rejection of pulmonary metastasis of tumor cells. 38 In the study of Poehlein et al, 31 adoptive transfer of effector T cells, which are taken from perforin and gIFN double knockout mice (PKO/GKO), mediated complete tumor regression and cured wild-type animals with established pulmonary metastasis of melanoma cells by a TNF-a mediated killing mechanism. In addition, Smyth et al 39 have reported that, using the Renca carcinoma tumor model, TRAIL expression on NK and NKT cells has effective antimetastatic functions in vivo mediated by a gIFNdependent immune mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Since perforin, gIFN and TNF-a were identified as critical pathways of effector mechanisms that characterize therapeutic anti-tumor T cells, 31 Hybridoma ascites containing specific antibodies against CD8, gIFN and TNF-a were intravenously injected into C57BL/6 and B6-PKO mice 1 day prior to inoculation of 39.5-B7 cells. Starting on day 6 after tumor cell inoculation, mice were further injected with hybridoma ascites weekly until local tumors were amputated.…”
Section: In Vivo Depletion Of Cd8 T-cells and Neutralization Of Tnf-amentioning
confidence: 99%
“…It has been reported that the mechanism of in vivo CD8 þ T-cell-mediated tumor regression is distinct from that of in vitro CD8 þ T-cell-mediated cytotoxicity, and is independent of perforin and FasL by using CD8 þ T cells with perforin gene knockout or FasL mutant 51,52 Recently, Hollenbaugh et al 53 demonstrated that CD8 þ T cell-secreted, but not the host-derived IFN-g play an important role in eradication of solid tumors by regulating CD8 þ T-cell expansion and migration and inducing tumor cell apoptosis. Blohm et al 54 visualized adoptive CD8 þ T-cell-mediated tumor destruction and found that tumors 'melt' from the inside were derived from destruction of tumor vasculature and accumulation of granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of in vivo therapeutic effect of the engineered T TNF cells observed in this study may not be due to its upregulated expression of perforin, but may be associated with its enhanced secretion of the transgenecoded human TNF-a as well as its elongated survival in vivo. TNF-a plays an essential role in CD8 þ T-cellmediated elimination of tumors in vivo 52,55 possibly by its direct cytotoxicity to tumor cells leading apoptosis through engagement of the p55 TNF-a receptor I. 56 The inflammatory cytokine TNF-a also activates macrophages, natural killer cells and T cells 20,57 by its binding to the p75 TNF-a receptor II (TNFRII).…”
Section: Discussionmentioning
confidence: 99%
“…An early study in mice revealed that rejection of pulmonary metastases by cultured tumorspecific CD8 T cells correlates better with their capacity to produce IFN-c than with their cytotoxicity in vitro [18]. More recent studies using IFN-c-deficient mice have provided compelling evidence for the important role of IFN-c in T cell-mediated tumor cell rejection [7,9,10,13,14,[19][20][21][22][23][24][25][26]. Various possibilities can be envisaged to explain the anti-tumor activity of IFN-c: first, IFN-c is known to increase MHC expression and antigen presentation, thereby rendering tumor target cells more susceptible to CTL attack [27][28][29].…”
Section: Introductionmentioning
confidence: 99%